Procalcitonin as a predictor of survival in patients with sepsis: A study on diagnostic accuracy - Abhishek Verma; Karan Kaushik; Amit Taluja; Pratik Shah (Heart Vessels and Transplantation, 2024)
Objective: Role of serum procalcitonin (PCT) in critically ill patients is well defined for identification of bacterial infection but it’s role in prediction of survival is not well established. We studied plasma kinetics of PCT, over the first three critical care days to validate its role in prediction of survival of patients with sepsis according to plasma level.